Study to evaluate the immunomodulatory effects of radiofrequency ablation compared to surgical resection for liver cancer - Mazmishvili, Ketevan (J Cancer, 2018)
Introduction: Hepatic cancer is a highly lethal tumour with increasing worldwide incidence. These tumours are characterized by the proliferation of malignant cells, generalised immunosuppression and chronic inflammation marked with an increase in inflammatory markers as a neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR) and overexpression of CD4+CD39+ on T lymphocytes. The studies have outlined immunomodulatory changes in liver cancer patients as the plausible explanation for the better survival. The aim of this pilot study was understand the possible immunomodulatory effect of radiofrequency (RF) energy and liver resection (non-radiofrequency based devices; non-RF device) in relation to NLR, PLR and expression of CD4+CD39+ T lymphocytes and compare the magnitude of these changes. Material and Methods: In the present study, 17 patients with hepatic cancer were prospectively divided into treatment groups radiofrequency ablation (RFA group) and Liver resection using non-RF devices (LR group). A blood sample was collected from each patient, one month before and after the procedure and compared with the blood samples of age-matched healthy volunteers for group wise comparison. The Mann-Whitney U test, Mc Nemar test and Wilcoxon rank test were used for statistical comparisons as appropriate. Results: A decrease in NLR was reported after RFA from 4.7±3.3 to 3.8±1.8 (P=0.283), in contrary to an increase from 3.5±2.8 to 4.5±3.2 (P=0.183) in LR group. Likewise, a decrease was discerned in PLR following RFA from 140.5±79.5 to 137±69.2 respectively (P=0.386) and increase in the LR group from 116±42.2 to 120.8±29 respectively (P=0.391). A significant decrease in CD4+CD39+ lymphocytes from 55.8±13.8 to 24.6±21.1 (P=0.03) was observed in RFA group whilst a significant increase was reported in LR group from 47.6±8.8 to 55.7±33.2 (P=0.38). Conclusion: Studies have shown that decrease in the NLR, PLR and expression of CD4+CD39+ on T lymphocytes as the marker of better survival in hepatic cancer patients and our findings have confirmed that these changes can be induced following application of RF energy. Moreover, this could be the explanation of better survival observed in different studies using RFA or other RF-based devices in comparison to non-RF based liver resection techniques. However, further larger studies are needed to confirm these findings.